Tuning Nanofiber Morphology and Hydrophobicity via PVDF-co-HFP Polymer Concentration - Naim, Naufaldin Adam; Rianjanu, Aditya (Greensusmater, 2025)
This study investigates the effect of poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP) concentration on the morphological and surface wettability properties of electrospun nanofibers. Nanofiber mats were fabricated using electrospinning with PVDF-co-HFP concentrations ranging from 12 wt% to 18 wt%. Scanning electron microscopy (SEM) analysis revealed that increasing polymer concentration resulted in larger and more uniform fiber diameters, ranging from approximately 235 nm to 560 nm. Fourier-transform infrared (FTIR) spectroscopy confirmed the preservation of the chemical structure, with characteristic peaks associated with CF₂ and C–F groups, and the presence of both α- and β-phases of PVDF. Water contact angle (WCA) measurements indicated a marked increase in hydrophobicity, with WCA values rising from ~108° for PVDF-co-HFP12 to ~128° for PVDF-co-HFP18. This enhancement is attributed to increased surface roughness and fiber diameter, in line with the Cassie–Baxter wetting model. The results demonstrate that polymer concentration is a critical parameter in tailoring nanofiber morphology and wettability, providing a straightforward strategy for designing functional materials in applications such as water-repellent coatings, filtration membranes, and sensing platforms.